Visualization analysis of feminist translation research in China (2002–2021) based on CiteSpace - Sun, Fei; Wang, Xiaochen; Li, Hongbin; Wang, Siying (Frontiers in Education, 2023)
Based on 601 papers on feminist translation theory published on China National Knowledge Infrastructure (CNKI) in the last 20 years from 2002 to 2021, this paper uses CiteSpace as a visual tool to draw a scientific knowledge map and makes a visual analysis of the research papers on feminist translation theory in China. It is found that 1) the cooperation between research institutions is not strong, and so is the authors; 2) the research focus detected mainly includes feminism, feminist translation theory, feminist translation, and translation; 3) according to the map of time zone and keywords mutation, this research field is constantly moving towards decline after fast development.